ASSESSING INVESTMENT ATTRACTIVENESS THROUGH SUSTAINABILITY CRITERIA IN TURBULENT ECONOMY - Petrov A.M.; Savkina R.V.; Kuzmina A.A.; Poluleh M.V.; Belousova T.A. (Scientific Journal of Pedagogy and Economics, 2020)
Driven by various economic forces, modern society develops rapidly. Millions of investment projects are implemented annually in all sectors of the economy, costing billions of dollars. Facing the unstable macroeconomic environment, Russia is more than ever concerned about effective investment management. Unfortunately, most investment strategies in Russia are implemented without properly assessing the investment attractiveness. Occasional investments cannot ensure the required long-term investment returns, which is one of the key performance indicators. Business viability in the medium and long run will be jeopardized if the management lacks the skill and competency to assess the investment attractiveness of its investees. Nonproductive investments would deteriorate the entity’s financial situation and affect its credibility with its shareholders and investors. It should be noted that sustainability analysis is a complex and comprehensive process. Each entity operates in a specific environment, which is subject to constant changes, both positive and negative. It is safe to say that positive changes, e.g. transitions and improvements in the social or environmental sphere, entail entity evolution due to the increased demand for its products and services. From the point of view of economic feasibility, an entity is aimed at deriving profit for itself and generating income for its shareholders. Surely, shareholders want the entity to be stable or even increasingly stable, thus, determining the need for its sustainable development. The relevance of the issues raised in this paper is explained by the importance of assessing the investment attractiveness of investees to effectively expand and adjust the entity’s product portfolio and improve the competitive performance of the economy in general.